The product space and evolution of international competitiveness—evidence from China’s strategic and critical mineral articles - Zhu, Wenxing; Hu, Tingting; Xiao, Wei; Liao, Jinping; Xu, Yue (Frontiers in Environmental Science, 2023)
Clarifying the evolution of international competitiveness for strategic and critical mineral articles is of great significance for promoting new energy development and achieving carbon neutrality in China. This study, therefore, calculates the series of indicators based on product space theory, for instance, international import & export shares, revealed comparative advantage (RCA) and product density, to analyze the competitiveness evolution. Results show that: the international competitiveness of China's strategic and critical mineral articles demonstrated a declining tendency, and the rising percentage of imports was much larger than the decreasing export percentage. The evolution of the international competitiveness of 11 strategic and critical minerals is different. Among them, the international competitiveness of two articles is very strong, that of four articles is relatively weak, and that of three products is decreasing trend. From the perspectives of industrial sectors and trade, we analyze the underlying reasons for the competitiveness evolution of 11 strategic and critical mineral articles in detail and discuss the industry transformation and upgrade feasibility for strategic and critical mineral articles. Our work aims to provide strong support for the upgrading and high-quality development of the strategic and critical mineral products industry by providing corresponding policy suggestions.